A Century of NU-Muhammadiyah in Indonesia: The Failure of Islamic Modernism? - Moeflich Hasbullah (Islamika Indonesiana, 2014)
Islamic modernism represented by Muhammadiyah and Persatuan Islam and Islamic traditionalism symbolized by Nahdlatul Ulama have lasted a century old in Indonesian history (1912-2014). The unavoidable tensions and conflicts between these two contrast Islamic movements occurred in various fields. The modernist hasbeen trying to promote their modern views and to eradicate tradition. On the contrary, the traditionalist has been working hard to maintain their Islamic tradition and fight for the modernist mission in disseminating their ideas. To some extent, the modernist is quite successful, however by comparative study methods applied in this article to see the result of these two Islamic streams, I argue that in common Islamic modernism has failed to weaken and to eradicate tradition as it was firstly introduced by their initiators over a century ago. The modernist is only successful in its attempt to build its own empire of modernism but without vanishing tradition. Rather than weakening, let alone disappearing, what has been occuring shows the opposite result. Islamic traditionalism even grows larger than modernist group and develops more dynamic in various fields. More than that, Islamic neo-traditionalism has emerged as its new variant, an intellectual movement that found a new land on the problems of modern spiritual drought.